Programma: 26 september Suicidal Tendencies; 28 september Saskia Laroo; 29 september Los Colores Del Flamenco; 2 oktober Bisserov Sisters
Programma: 26 september Suicidal Tendencies; 28 september Saskia Laroo; 29 september Los Colores Del Flamenco; 2 oktober Bisserov Sisters.